Comparative Outcome of Acute Coronary Syndrome In Diabetics and Non-diabetics (Journal of Chittagong Medical College Teachers' Association, 2018)
Background : It is well known that Coronary Artery Disease (CAD) is strongly associated with Diabetes Mellitus (DM). When CAD develops in diabetic patients the incidence of Acute Coronary Syndrome (ACS) becomes double. Diabetics also suffer more heart failure, pulmonary edema & renal failure while in hospital. The proportion of ACS in diabetic patients is increasing. This trend will likely continue because the population has become more sedentary and overweight. A few studies available comparing the various outcomes of ACS patients with & without DM in our country yet we know that burden of both ACS and DM in our population is increasing. Materials and methods: This analytical study was conducted from July, 2013 to June, 2104 in the Department of Cardiology of Chittagong Medical College Hospital. Subjects were by purposive sampling and grouped into two groups as diabetic (Group A) & non diabetic (Group B) each group had 100 patients. Data processing and analysis was done with the help of computer using statistical software SPSS version-17 for windows. Statistical analyses were done by appropriate tests of significances (i.e. t-test, chi-square test). Results: The diabetic group had a significantly higher mean age (52.84 ±8.40 years) compared to the non-diabetic group (47.96 ± 9.52) (p=0.000) and majorities of the patients were male. Raised level of Serum Troponin I and mean LVEF was highly significant between the groups. The patients of both groups developed cardiogenic shock and heart failure in a different proportion (10 % and 4%: p= 0.042) which was statistically significant. Arrhythmia was an outcome in both groups without significant difference and recurrent angina was only found in diabetic group (n=06). Conclusion: Our study revealed higher number of complications, mortality and worse clinical features in diabetic ACS patients determining the additional adversities and complicated management with a lower prognostic outcome.JCMCTA 2018 ; 29 (1) : 28-34